Restructuring PayLater Regulations to Promote Consumer Justice - Johannes Adrian Marpaung; Peter Gideon Michael Tarigan; Graciela Graciela; Bayu Widianto (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid growth of PayLater services as a digital financing instrument has significantly enhanced financial inclusion and facilitated consumer transactions. However, this development has also generated various legal challenges due to inadequate regulatory frameworks and insufficient consumer protection mechanisms. This study aims to analyze the implementation of PayLater services in Indonesia, identify legal obstacles and regulatory gaps in consumer protection, and formulate strategies for improving governance and regulatory arrangements. The study employs a normative juridical method using statutory, conceptual, and comparative approaches through a comprehensive review of primary, secondary, and tertiary legal materials. The findings reveal that the regulation of PayLater services remains fragmented, resulting in legal uncertainty concerning fee transparency, personal data protection, debt collection practices, and dispute resolution mechanisms. The study concludes that the establishment of specific regulations, harmonization of regulatory authority, strengthening of supervisory mechanisms, and the development of an integrated consumer protection framework are essential to ensuring legal certainty, justice, and the sustainability of Indonesia’s digital financing ecosystem.